PENILAIAN PLACEMAKING DI RUANG TERBUKA PUBLIK KAWASAN JAM GADANG - Hardi, Resty Aprila; Pramitasari, Diananta (Unika Santo Thomas, 2023)
Jam Gadang is a landmark of Bukittinggi City so it becomes a tourist destination. The concentration of visitors in Jam Gadang Plaza makes Jam Gadang very crowded, especially during the holiday. Moreover, it impacts the activities of visitors, which cannot be accommodated at the same time by the public open space of Jam Gadang. Although there are 2 other public open spaces near Jam Gadang Plaza, which are Bung Hatta Monument Park and Pahlawan Tak Dikenal Monument Park, the two public open spaces cannot have a role in receiving some of Jam Gadang Plaza's visitors. This research was conducted to find out how the quality of public spaces in the Jam Gadang area according to the placemaking assessment. The research method used place-centered mapping, questionnaires dissemination, and interviews. The results of the placemaking assessment showed that Jam Gadang Plaza has a